THE NATURAL STANDPOINT AND SCHÜTZ’S SOCIAL WORLD - Nerija Putinaitė (Problemos)
The Natural Standpoint allows for two possible ways of treating the social world: the first, to take it as a finished product for passive investigation, and the second, to take it as a place of action. The chance to overstep the sharp distinction between social observer and social actor is exluded. Schütz’s phenomenological sociology presents the third way, reconciling these two positions. The social world is not merely a finished and (only) observable construction, nor a space of unreflective action. It is continuously in the process of creation, executed by active social observers.